A MANAGEMENT OF SPEAKING CLASS STUDY AT SMART ILC PARE KEDIRI - Mustafah, Mustafah (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2020)
The teacher English is challenged should be able to manage the classroom. Descriptive qualitative was the design of this research because a management of speaking class at SMART ILC that was unique. The data collecting method were observation, interview and documentation. The result of this research showed that the tutor strategy in teaching speaking was seating arrangement was strategy to position a good learning pattern for delivering the material as well with the capture of a student seating strategy that is used semicircle, Oral content strategy before starting lesson was done in rotation to remember the material that has been studied. The teaching method of speaking in the outdoors to make students enjoy learning and the atmosphere is cool in the open and surrounded by shady trees. The ability of students in speaking was capability, ability and understanding students that was different every student. A student response about that strategy in teaching speaking that was students and teacher response about strategy is very unique. The teaching strategies used are very effective because students enjoy the teaching methods provided.